'Don't Stop Me Now': Mobility and Cosmopolitanism in the Bourne Saga. (14th March 2016) - Azcona, María del Mar
Abstract: This article explores the search for identity of the main character of the Jason Bourne movies in the light of contemporary critical theories on mobility and cosmopolitanism. This theoretical framework is combined with close textual analysis of the films in order to explore the visual and narrative mechanisms that the three Bourne movies starring Matt Damon use in order to, first, capture the protagonist's lost sense of self and, second, construct a new cosmopolitan hero for the mainstream. As I argue, Bourne's unrelentless journey across borders encapsulates some of the paradoxes of our highly mobile times, while also calling attention to certain shortcomings and inadequacies of the 'national paradigm', to make sense of an individual's existence within contemporary societies.